ANALISIS PEMILIHAN MODA TRANSPORTASI ONLINE DAN TRANSPORTASI KONVENSIONAL DI KOTA DENPASAR (Contoh Kasus: Go-Car dan Sarbagita) - Ni Ketut Sri Astati Sukawati; Cokorda Putra Wirasutama; Rosnyati Cartona (Program Studi Teknik Sipil Fakultas Teknik Universitas Mahasaraswati Denpasar, 2021)
Transportation is very necessary to meet the main needs of society in general in Denpasar, such as the need for education, health, economy, and social. Currently, there are various choices of vehicles or modes of transportation that you want to use to reach your destination, be it online transportation (Go-Car) or conventional transportation (Sarbagita). The choice of transportation modes in Denpasar City aims to find out the factors that influence the community in choosing the online mode of transportation (Go - Car) and conventional transportation (Sarbagita). The questionnaire in this study was in the form of google form and then distributed via online media to respondents and processed using a multiple linear regression analysis approach with the help of the SPSS V25 program. The results of the study of 100 respondents were 94 respondents who chose the online mode of transportation (Go-Car) and 6 respondents who chose the conventional mode of transportation (Sarbagita). From the results of the data analysis shows that the variable transportation cost variation (x1) affects the community in choosing the transportation mode in Denpasar City by 21% with the choice of conventional transportation mode (Sarbagita), variations in waiting time (x2) affect the community in choosing the mode of transportation in Denpasar City. 58.5% with the choice of online transportation mode (Go-Car), variations in the level of comfort (x3) affecting the community in Denpasar City by 17.3% with the choice of online transportation mode (Go-Car).